Analysis of the redox state of patients acetilsalicylic acid users (Research, Society and Development, 2022)
One of the major global health problems is chronic non-transmissible diseases such as heart and coronary diseases, diabetes, hypertension, among others, leading to a high number of premature deaths and physiological changes related to oxidative metabolism, causing excessive increases in the production of oxigen reactive species. The objective of this study was to analyze the redox status of patients with acetylsalicylic acid (AAS) users with healthy and volunteer subjects in the same pathological conditions, but not users of the medication, through the antioxidant analyzes of the levels of GSH, TBARS and total serum antioxidant capacity (TEAC). The study included volunteers aged 19-96 and AAS users for more than one year. Analyzes of GSH levels showed a significant decrease in volunteers with coronary disorders. In the analysis of TBARS and TEAC levels, there was an increase in the lipid peroxidation activity and a decrease in the TEAC in the non-users of the medication. The observations made regarding the embrittlement of the antioxidant system can not be directly related to the use of the drug in question, since biological and environmental factors must be taken into account, for such studies under controlled conditions should be carried out to determine the direct relation between drug use and oxidant activity.